PENDAYAGUNAAN HAK BANTUAN HUKUM BAGI TERSANGKA DI TINGKAT PENYIDIKAN - -, Supriyanta - (RESPONSA, 2010)
AbstractA set of rights a legal advisers in assisting the accused at the level of investigationaccording to the Criminal Procedure Law of 1981 should have more explainationaccording to their position as legal advisers. The Criminal Procedure Las of 1981still contains weaknesses and discrepancies in relation with the regulation of therights concerning legal aid at the level of investigation.